Guanidine acetic acid exhibited greater growth performance in younger (13–30 kg) than in older (30–50 kg) lambs under high-concentrate feedlotting pattern - Li, Wen-Juan; Wu, Qi-Chao; Cui, Zhao-Yang; Jiang, Yao-Wen; Aisikaer, Ailiyasi; Zhang, Fan; Chen, He-Wei; Wang, Wei-Kang; Wang, Yan-Lu; Lv, Liang-Kang; Xiong, Feng-Liang; Liu, Ying-Yi; et al. (Frontiers in Veterinary Science, 2022)
Guanidine acetic acid (GAA) is increasingly considered as a nutritional growth promoter in monogastric animals. Whether or not such response would exist in rapid-growing lambs is unclear yet. The objective of this study was to investigate whether dietary supplementation with uncoated GAA (UGAA) and coated GAA (CGAA) could alter growth performance, nutrient digestion, serum metabolites, and antioxidant capacity in lambs. Seventy-two small-tailed Han lambs initially weighed 12 ± 1.6 kg were randomly allocated into six groups in a 2 × 3 factorial experimental design including two forage-type rations [Oaten hay (OH) vs. its combination with wheat silage (OHWS)] and three GAA treatment per ration: no GAA, 1 g UGAA, and 1 g CGAA per kg dry matter. The whole experiment was completed in two consecutive growing stages (stage 1, 13–30 kg; stage 2, 30–50 kg). Under high-concentrate feeding pattern (Stage 1, 25: 75; Stage 2, 20: 80), UGAA or CGAA supplementation in young lambs presented greater dry matter intake (DMI) in stage 1 and average daily gain (ADG) in the whole experimental period; lambs in OH group had higher ADG and DMI than that in OHWS group in stage 1 and whole experimental period, but this phenomenon was not observed in stage 2. Both UCGA and CGAA addition increased dietary DM, organic matter (OM), neutral detergent fiber (NDF), and acid detergent fiber (ADF) digestion in both stages. In blood metabolism, UCGA and CGAA addition resulted in a greater total protein (TP) and insulin-like growth factor 1(IGF-1) levels, as well as antioxidant capacity; at the same time, UCGA and CGAA addition increased GAA metabolism-creatine kinase and decreased guanidinoacetate N-methyltransferase (GAMT) and L-Arginine glycine amidine transferase catalyzes (AGAT) activity. In a brief, the results obtained in the present study suggested that GAA (UGAA and CGAA; 1 g/kg DM) could be applied to improve growth performance in younger (13–30 kg) instead of older (30–50 kg) lambs in high-concentrate feedlotting practice.